Preparation method and device of hydroxyapatite doped zinc-copper powder metallurgy degradable bone implant material

Through hydroxyapatite-doped zinc-copper powder metallurgy technology, the problem of slow degradation rate of zinc alloys is solved, and the rapid degradation and efficient bone formation of zinc-based bone implant materials are achieved, improving its mechanical and antibacterial properties.

CN119525501AInactive Publication Date: 2025-02-28ZHEJIANG IND & TRADE VOCATIONAL & TECH COLLEGE (ZHEJIANG IND & TRADE TECHNICIAN COLLEGE)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510096576.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The degradation rate of zinc alloy is too slow, and the mechanical properties, osteogenic and antibacterial properties are insufficient, resulting in the biodegradation rate of zinc-based bone implant materials in the body.

Method used

The metallurgy technology of hydroxyapatite-doped zinc-copper powder is used to prepare tough zinc-based composite materials by mechanically doping hydroxyapatite powder and atomized Zn-xCu alloy powder, and high-frequency vibration and hot extrusion molding technology.

Benefits of technology

Significantly accelerate the internal and external degradation of zinc-based bone implant materials, improve their mechanical properties, osteogenic properties and antibacterial properties, and meet the rapid degradation and efficient osteogenic needs of bone implant materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525501A_ABST
    Figure CN119525501A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical metal, and particularly relates to a preparation method of a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, which comprises the following steps: firstly putting steel wool into a cold pressing mold, then filling alloy powder doped with hydroxyapatite powder into the periphery of the steel wool, and carrying out cold pressing on the alloy powder; then a green body is obtained through vibration and compression molding, the green body is sintered to obtain a powder metallurgy part, the powder metallurgy part is subjected to heat preservation and then subjected to hot extrusion molding, then a round rod is cut into a square rod, preheating and hot rolling are conducted, and finally a hot-rolled plate sample or a hot-rolled foil sample is obtained after air cooling; a matrix material can be strengthened and toughened by adopting heterogeneous material fiber reinforcement, galvanic corrosion can be caused by the difference between standard electrode potentials of the two materials, in-vivo and in-vitro degradation of the zinc-based bone implant material is accelerated, and based on the osteogenesis performance improvement requirement, the osteogenesis performance of the implant material can be remarkably improved by additionally adding osteogenesis particles such as hydroxyapatite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical metals, and in particular relates to a preparation method and a device for a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material. Background Art

[0002] In recent years, since the standard electrode potential of zinc is lower than that of iron and higher than that of magnesium, zinc alloys have a degradation rate between Mg alloys and Fe alloys, and their corrosion products can be metabolized or digested. Zinc has important physiological functions, participating in nucleic acid metabolism and stimulating bone formation, which is important for bone healing; zinc alloys have good machinability, low melting point and low oxygen reactivity; in addition, zinc alloys are radiopaque, so coronary stents can be made visible by fluoroscopy without marking, however, zinc has low strength and small plastic deformation; developing high-strength and high-ductility zinc alloys is one of the goals of scientists.

[0003] Based on the problem of poor strength of zinc, alloying with Fe, Mg, Ti and Cu can improve its strength, while adding TCP, HA, etc. can improve the bone integration and biocompatibility of zinc alloys. Compared with casting, the powder metallurgy method has no solubility limitation. It is worth noting that the introduction of Cu can further improve the antibacterial performance and ductility, which is particularly important for the application of bone implant materials. At the same time, since Zn consumes oxygen during the degradation process and the blood supply to the bone repair microenvironment is limited, the oxygen delivery in the local area is delayed, resulting in its biodegradation in the body being slower than in vitro. Therefore, compared with the tissue healing time, the in vivo biodegradation rate of zinc-based bone implant materials is too slow. Therefore, the strengthening, degradation regulation, osteogenesis and antibacterial performance improvement of zinc-based powder metallurgy bone implant materials are also urgent issues to be addressed. Summary of the invention

[0004] The purpose of the present invention is to provide a method and device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material in view of the above-mentioned technical problems, so as to solve the problems of slow degradation rate of zinc alloy and insufficient mechanical properties, osteogenesis and antibacterial properties.

[0005] In view of this, the present invention provides a method for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, comprising the following steps: S1: Steel wool with a diameter of 30 μm is evenly placed in a cylindrical cold pressing mold with a diameter of 40 mm; S2: filling the alloy powder mechanically doped with hydroxyapatite powder around the steel wool; S3: The cold pressing mold is vibrated at high frequency for 10 minutes so that the alloy powder fully fills the cold pressing mold and the height of the upper layer of powder is flush with the steel wool; S4: pressing and molding in a cold pressing mold at a pressure of 5-50 MPa and maintaining the pressure for 5-20 minutes to obtain a green body; S5: placing the green body in S4 in a muffle furnace heated to 250-350° C. and sintering for 0.5-2 hours to obtain a powder metallurgy part; S6: The powder metallurgy part in S5 is placed in a muffle furnace heated to 250-380°C for 0.5-1 hour, and then quickly placed in an extrusion barrel with an extrusion ratio of 16:1, and hot extruded at a speed of 30 mm / s using a twin-shaft extruder to obtain a round rod with a diameter of 10 mm; S7: Use wire cutting to symmetrically cut the round rod in S6 into square rods with a thickness of 4-6 mm and a length of 100 mm, and then put them into a muffle furnace heated to 200-350°C and preheat for 0.5-2 hours; S8: hot rolling the square bar to a hot rolled plate with a total reduction of 50-95% by 2-10% reduction per pass, and preheating in a muffle furnace for 5 minutes between each pass; S9: After air cooling to room temperature, obtain a hot-rolled plate sample or a hot-rolled foil sample.

[0006] In the above technical solution, further: The particle size of the mechanically doped hydroxyapatite powder in the alloy powder in S2 is 0.05~2μm, and the mass ratio is 0.5~15%.

[0007] In the above technical solution, further: The alloy powder in S2 is atomized Zn-xCu (x=0.2~10wt.%) alloy powder, and the particle size is 30~1000 mesh.

[0008] In the above technical solution, further: In S2, the mass ratio of steel wool to Zn-xCu alloy powder is 1:2~30.

[0009] The present invention provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, comprising: The base is provided with a bottom template, a cold pressing mold is provided on the bottom template, and the cold pressing mold is provided with a cavity; The vibration mechanism is installed on the base and is located on the side of the bottom mold plate, and includes a lifting component for lifting the cold pressing mold and a knocking component for vibrating the cold pressing mold; The upper template is installed above the bottom template in a lifting manner, and is provided with an upper mold corresponding to the cold pressing mold, and a core adapted to the cavity is installed on the upper mold.

[0010] In the above technical solution, further, the lifting assembly includes: A clamping jaw is slidably connected to the base and is used to clamp the cold pressing mold; A first driving member, mounted on the base and used for the first driving jaw to slide on the base; The lifting member is installed at the end of the clamping jaw away from the cold pressing die and is used to drive the clamping jaw to lift.

[0011] In the above technical solution, further, the striking component includes: a bracket mounted on the clamping jaw; The striking head is slidably mounted on the bracket, and one end of the striking head extends out of the bracket to strike the side of the cold pressing mold; A first spring is installed in the bracket and is used to push the striking head to strike the side of the cold pressing die; The electromagnet is installed in the bracket and is used to attract the striking head to compress the first spring when power is supplied; An electric control unit, installed in the bracket and used to turn the electromagnet on and off; The second driving member is mounted on the clamping jaw and is used to drive the electric control unit to sequentially switch the electromagnet on and off.

[0012] In the above technical solution, further, the electric control component includes: The fixed electrical contact is mounted on the bracket and includes a first electrical contact and a second electrical contact which are arranged correspondingly, and an electrical gap is formed between the first electrical contact and the second electrical contact; A disc is mounted at the output end of the second driving member and is provided with a movable electrical contact capable of rotating with the disc and being embedded in the electrical gap for connecting or disconnecting the first electrical contact and the second electrical contact; The first electrical contact and the second electrical contact are electrically connected to two connection terminals on the electromagnet respectively.

[0013] In the above technical solution, further: The movable electrical contacts include conductive contacts and non-conductive contacts, and are provided in plurality and are arranged on the disc at equal intervals around the circumference; Among them, there are multiple knocking components, which are arranged around the cold pressing mold, and a neutral point is formed between two adjacent fixed electrical contacts, so that when the non-conductive contacts correspond to them, all electromagnets are energized.

[0014] In the above technical solution, further, it also includes: The limiting protrusion is installed on the side wall of the cold pressing mold on the bottom template, and the bottom template is provided with a mounting groove for embedded installation of the limiting protrusion; A second spring is arranged in the installation groove, and two ends thereof are respectively in contact with the inner wall of the installation groove and the limiting protrusion; A top block is mounted on the bottom wall of the cold pressing die of the bottom template; The third spring is arranged in the bottom template, and two ends thereof are respectively in contact with the bottom template and the top block.

[0015] The beneficial effects of the present invention are: 1. The use of heterogeneous fiber reinforcement can not only strengthen the matrix material, but also cause galvanic corrosion based on the difference in standard electrode potential between the two materials, thereby accelerating the degradation of zinc-based bone implant materials in vivo and in vitro.

[0016] 2. Based on the need to improve osteogenesis, in addition to the release of Zn ions in the matrix material to promote osteogenesis, the addition of osteogenic particles such as hydroxyapatite (HA), β-TCP, zinc phosphate (ZnP) can significantly improve the osteogenesis of implant materials.

[0017] 3. In addition, by adding Cu elements to the matrix, it is possible to further cooperate with Zn ions to exert a stronger antibacterial effect on the basis of improving the anti-aging performance of zinc-based bone implant materials.

[0018] 4. By setting a vibration mechanism in the cold pressing mold, the convenience of filling the gaps in the steel wool with alloy powder is improved, and there is no need for separate vibration mixing, which effectively improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the XRD spectrum of the Fe / ZC and Fe / ZC-HA composite material samples in the state of hot extrusion and hot rolling of the present invention; Figure 2 The chemical composition analysis diagrams of the hot extruded and hot rolled Fe / ZC-HA composite material sample of the present invention are shown by SEM, EDS line scanning, surface scanning and point scanning; Figure 3 It is the metallographic structure diagram of the Fe / ZC and Fe / ZC-HA composite material samples in the state of hot extrusion and hot rolling of the present invention; Figure 4 The mechanical properties of the Fe / ZC and Fe / ZC-HA composite materials samples in hot extrusion and hot rolling state after room temperature tensile and bending tests of the present invention are shown; Figure 5 It is the polarization curve diagram of the hot extruded and hot rolled Fe / ZC and Fe / ZC-HA composite material samples in Hanks' and DMEM solutions of the present invention; Figure 6 It is the electrochemical performance parameter of the hot extruded and hot rolled Fe / ZC and Fe / ZC-HA composite material samples fitted after the polarization test of the present invention; Figure 7 It is a schematic diagram of the structure of the device of the present invention; Figure 8 is a top view of the device of the present invention; Fig. 9 The present invention Figure 8 Sectional view at AA in the middle; Fig.10 The present invention Fig. 9 Enlarged view of point C in the middle; Fig.11 The present invention Fig. 9 Sectional view at the middle BB; Fig.12 The present invention Fig.11 The enlarged view of point D in the middle; The markings in the figure are as follows: 1. base; 2. bottom template; 3. cold pressing mold; 4. cavity; 5. lifting assembly; 50. clamping claw; 51. first driving member; 52. lifting member; 6. knocking assembly; 60. bracket; 61. knocking head; 62. first spring; 63. electromagnet; 64. electric control unit; 640. fixed electrical contact; 641. electrical gap; 642. disk; 643. moving electrical contact; 644. neutral point; 65. second driving member; 7. upper template; 8. upper mold; 9. core; 10. limiting protrusion; 11. mounting groove; 12. second spring; 13. top block; 14. third spring. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.

[0021] Embodiment 1: This embodiment provides a method for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, comprising the following steps: S1: Steel wool with a diameter of 30 μm is evenly placed in a cylindrical cold pressing mold with a diameter of 40 mm; S2: filling atomized Zn-2Cu alloy powder with a size of 100 mesh and mechanically doped with hydroxyapatite powder with a particle size of 0.2 μm and a mass ratio of 3% around steel wool, and controlling the mass ratio of steel wool to Zn-2Cu alloy powder to be 1:10; S3: The cold pressing mold is vibrated at high frequency for 10 minutes so that the alloy powder fully fills the cold pressing mold and the height of the upper layer of powder is flush with the steel wool; S4: Pressing and molding in a cold pressing mold at a pressure of 50 MPa and maintaining the pressure for 10 minutes to obtain a cylindrical steel wool reinforced zinc-based composite green body; S5: placing the cylindrical steel wool reinforced zinc-based composite green body in a muffle furnace heated to 320° C. and sintering for 1 hour to obtain a steel wool reinforced Zn-2Cu-3HA (referred to as Fe / ZC-3HA) composite powder metallurgy part; S6: The steel wool-reinforced Zn-2Cu-3HA composite powder metallurgy part was placed in a muffle furnace heated to 380°C for 0.5 hours, and then quickly placed in an extrusion barrel with an extrusion ratio of 16:1, and hot extruded at a speed of 30 mm / s using a twin-shaft extruder to obtain a round rod with a diameter of 10 mm; S7: Use wire cutting to symmetrically cut the round rod in S6 into square rods with a thickness of 5 mm and a length of 100 mm, and then put them into a muffle furnace heated to 340°C for preheating for 0.5 hours; S8: hot rolling the square bar to a hot rolled plate with a total reduction of 80% by 5% reduction in each pass, and preheating in a muffle furnace for 5 minutes between each pass; S9: After air cooling to room temperature, a hot rolled plate sample is obtained; At the same time, under the above process, steel wool reinforced Zn-2Cu composite powder metallurgy parts (referred to as Fe / ZC) without adding hydroxyapatite (HA) were used as a comparison.

[0022] After the test in this embodiment, it can be seen that the XRD spectra of the hot extruded and hot rolled Fe / ZC and Fe / ZC-3HA composite samples (such as Figure 1 ) contain α-Zn, CuZn5, α-Fe, FeZn 13 and a small amount of ZnO phase; In addition, the Fe / ZC-HA composite sample also contains HA phase; SEM and EDS chemical composition analysis of the longitudinal section of the hot extruded and hot rolled Fe / ZC-HA composite sample (such as Figure 2 ) shows that there is an obvious transition layer structure at the interface between steel wool and matrix, showing good bonding performance (such as Figure 2 (a in the middle); EDS line scanning analysis from steel wool to matrix phase (such as Figure 2 (b) shows that the Fe content gradually decreases, the Zn content gradually increases, and the Fe and Zn content of the transition layer are evenly distributed, indicating that the Fe and Zn elements diffuse with each other; EDS point scanning analysis (such as Figure 2 c in the middle) and combined with XRD analysis, it can be seen that the matrix phase (point 1) is α-Zn phase, the fine second phase (point 2) is CuZn5 phase, and the second phase of the transition layer (points 3 and 4) is FeZn 13 phase, the steel wool (point 5) is the α-Fe phase, and the black second phase (point 6) is the HA phase; EDS surface scanning analysis (such as Figure 2 (d) shows that there are a lot of Zn and Fe elements in the matrix phase and steel wool, while there are two kinds of element contrasts of Zn and Fe in the transition layer, indicating that the transition layer is a second phase containing Zn and Fe; it is worth noting that the black phase contains a lot of Ca, P and O elements; The metallographic structures of Fe / ZC and Fe / ZC-3HA composite samples after hot extrusion and hot rolling (such as Figure 3 ) shows that there are fibrous strip-shaped steel wool and streamlined matrix phase structures along the rolling direction (RD) on the surface and cross section of the sample, and there is an obvious irregular FeZn 13 phase transition layer; In addition, the Fe / ZC-3HA composite samples also have a black streamlined HA phase; the mechanical properties of the hot extruded and hot rolled Fe / ZC and Fe / ZC-3HA composite samples (such as Figure 4 ) showed that the tensile strength of the Fe / ZC composite sample was 386 MPa, the yield strength was 295 MPa, the elongation was 40.6%, and the flexural yield strength was 427 MPa; in comparison, the Fe / ZC-3HA composite had higher strength and slightly lower elongation (tensile strength was 399 MPa, yield strength was 306 MPa, elongation was 36.2%, and flexural yield strength was 439 MPa), indicating that HA helps to improve the mechanical strength; Polarization curves of hot extruded and hot rolled Fe / ZC and Fe / ZC-3HA composite samples in Hanks' and cell culture medium (DMEM+10% fetal bovine serum, referred to as DMEM) solutions (e.g. Figure 5 ) and the corresponding electrochemical performance parameters (such as Figure 6 ) showed that the corrosion potential, corrosion current density, corrosion rate and degradation rate of Fe / ZC-3HA composite material after immersion test for 30 days were -1.022 V SCE , 80.0μA / cm2, 1167μm / y and 96.1μm / y, the corrosion rate and corrosion potential increased relative to those of the Fe / ZC composite, indicating that HA can further regulate the degradation rate of the Fe / ZC composite; At the same time, compared with Hanks' solution, the degradation rate in DMEM solution is lower and the corrosion potential is larger, indicating that the degradation rate of hot-extruded and hot-rolled Fe / ZC and Fe / ZC-3HA composite samples will be slowed down in DMEM solution; The hemolysis rates of the 100% hot-extruded and hot-rolled Fe / ZC and Fe / ZC-3HA composite extracts in rat blood were 2.6 and 3.2%, respectively, meeting the requirement that the hemolysis rate of clinical medical materials should be less than 5%. After culturing L929 mouse fibroblasts in 100%, 50% and 25% concentrations of hot extruded and hot rolled Fe / ZC and Fe / ZC-3HA composite extracts for 3 days, the cell viability was 36.6 and 32.5%, 82.9 and 90.8%, 91.5 and 103.2%, respectively, indicating that the diluted extracts had good cell compatibility (cell viability greater than 80% was non-cytotoxic). After culturing NIH-3T3 mouse fibroblasts in 25% concentration hot extrusion combined with hot rolling Fe / ZC and Fe / ZC-3HA composite extracts for 7 days, the ALP activity was 1.9 and 3.3 times higher than that in pure culture medium, respectively, indicating that HA can promote the improvement of osteogenic differentiation performance; The inhibition zone sizes of the hot-extruded and hot-rolled Fe / ZC and Fe / ZC-3HA composites after co-culture with Staphylococcus aureus for 1 day were 5.9 and 6.7 mm, respectively, showing excellent antibacterial properties (an inhibition zone diameter greater than 1 mm indicates significant antibacterial properties).

[0023] Embodiment 2: This embodiment provides a method for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, comprising the following steps: S1: Steel wool with a diameter of 30 μm is evenly placed in a cylindrical cold pressing mold with a diameter of 40 mm; S2: filling the atomized Zn-2Cu alloy powder with a size of 100 mesh and mechanically doped with hydroxyapatite powder with a particle size of 0.2 μm and a mass ratio of 5% around the steel wool, and controlling the mass ratio of the steel wool to the Zn-2Cu alloy powder to be 1:20; S3: The cold pressing mold is vibrated at high frequency for 10 minutes so that the alloy powder fully fills the cold pressing mold and the height of the upper layer of powder is flush with the steel wool; S4: Pressing and molding in a cold pressing mold at a pressure of 50 MPa and maintaining the pressure for 10 minutes to obtain a cylindrical steel wool reinforced zinc-based composite green body; S5: placing the cylindrical steel wool reinforced zinc-based composite green body in a muffle furnace heated to 320° C. and sintering for 2 hours to obtain a steel wool reinforced Zn-2Cu-5HA (referred to as Fe / ZC-5HA) composite powder metallurgy part; S6: The steel wool reinforced Zn-2Cu-5HA composite powder metallurgy part was placed in a muffle furnace heated to 360°C for 0.5 hours, and then quickly placed in an extrusion barrel with an extrusion ratio of 16:1, and hot extruded at a speed of 30 mm / s using a twin-shaft extruder to obtain a round rod with a diameter of 10 mm; S7: Use wire cutting to symmetrically cut the round rod in S6 into square rods with a thickness of 4 mm and a length of 100 mm, and then put them into a muffle furnace heated to 320°C for preheating for 1 hour; S8: hot rolling the square bar to a hot rolled plate with a total reduction of 95% by 5% reduction in each pass, and preheating in a muffle furnace for 5 minutes between each pass; S9: After air cooling to room temperature, a hot rolled foil sample is obtained; After the test of this embodiment, it can be known that the tensile strength of the hot extruded and hot rolled Fe / ZC-5HA composite foil sample is 399 MPa, the yield strength is 304 MPa, the elongation is 33.4%, and the bending yield strength is 453 MPa; The corrosion potential, corrosion current density, corrosion rate and degradation rate of the hot extruded and hot rolled Fe / ZC-5HA composite foil samples in Hanks' and DMEM solutions and immersion test for 30 days were -1.011 and -0.980 V, respectively. SCE , 85.0 and 45.6 μA / cm2, 1244 and 667 μm / y, 99.4 and 55.8 μm / y, indicating that HA and rolling deformation can further regulate the degradation rate of the composites; The hemolysis rate of the 100% concentration hot extruded and hot rolled Fe / ZC-5HA composite material extract in rat blood was 3.6%, which meets the requirement of clinical medical material hemolysis rate less than 5%. After culturing L929 mouse fibroblasts in the extracts of hot-extruded and hot-rolled Fe / ZC-5HA composites at concentrations of 100%, 50%, and 25% for 3 days, the cell viability was 30.7%, 92.9%, and 105.1%, respectively, indicating that the diluted extracts had good cell compatibility. After culturing NIH-3T3 mouse fibroblasts in the 25% concentration of hot extrusion and hot rolling Fe / ZC-5HA composite extract for 7 days, the ALP activity was 3.7 times higher than that in the pure culture medium, indicating that HA can promote the improvement of osteogenic differentiation performance; The inhibition zone size of the hot-extruded and hot-rolled Fe / ZC-5HA composite material was 7.5 mm after co-culture with Staphylococcus aureus for 1 day, showing excellent antibacterial properties.

[0024] Embodiment 2: This embodiment provides a method and apparatus for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, comprising: A base 1 is provided with a bottom template 2, a cold pressing mold 3 is provided on the bottom template 2, and a cavity 4 is provided in the cold pressing mold 3; The vibration mechanism is installed on the base 1 and is located on the side of the bottom mold plate 2, and includes a lifting component 5 for lifting the cold pressing mold 3 and a knocking component 6 for vibrating the cold pressing mold 3; The upper mold plate 7 is installed in a lifting manner above the bottom mold plate 2 and is provided with an upper mold 8 corresponding to the cold pressing mold 3 , and a core 9 adapted to the mold cavity 4 is installed on the upper mold 8 .

[0025] It can be seen from this embodiment that by setting a vibration mechanism in the cold pressing mold 3, the convenience of filling the gaps of the steel wool with alloy powder is improved, and there is no need for separate vibration mixing, which effectively improves the production efficiency; At the same time, the lifting assembly 5 can lift the cold pressing mold 3 so that when it is knocked, it can avoid being affected by the bottom mold plate 2 and avoid affecting the entire device, thereby ensuring the stability of the device.

[0026] Embodiment 3: This embodiment provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material. In addition to the technical solutions of the above embodiments, it also has the following technical features. The lifting component 5 includes: The clamping jaw 50 is slidably connected to the base 1 and is used to clamp the cold pressing mold 3; A first driving member 51 is mounted on the base 1 and is used to drive the first clamping jaw 50 to slide on the base 1; A lifting member 52 is installed at one end of the clamping jaw 50 away from the cold pressing die 3 and is used to drive the clamping jaw 50 to lift; The clamping jaw 50 can be slidably connected to the base 1 by a slider and a slide rail, and the first driving member 51 can be a cylinder to push the clamping jaw 50 eastward, and the lifting member 52 is arranged between the slider and the clamping jaw 50, and can be a hydraulic cylinder or a cylinder; At the same time, two clamping jaws 50 are used, that is, they are symmetrically located on both sides of the cold pressing mold 3, and they are close to each other to clamp the cold pressing mold 3, and after clamping, the cold pressing mold 3 is lifted under the action of the lifting member 52; In addition, a rubber elastic pad and a cover plate are provided on one side of the clamping jaws 50 close to the cold pressing mold 3 , and the cover plate can seal the cavity 4 of the cold pressing mold 3 after the two clamping jaws 50 clamp the cold pressing mold 3 .

[0027] It can be seen from this embodiment that by adopting the above-mentioned first driving member 51 and lifting member 52, it is convenient to lift the cold pressing mold 3, the structure is simple, the operation is convenient, and the two clamping jaws 50 symmetrically on both sides of the cold pressing mold 3 are clamped, which can effectively improve the stability; At the same time, the setting of the elastic pad can reduce the vibration transmitted to the clamping jaw 50 when the cold pressing mold 3 vibrates, effectively ensuring the stability of the device, and the cover plate can prevent the alloy powder from falling out of the cold pressing mold 3 when the cold pressing mold 3 is vibrated.

[0028] Embodiment 4: This embodiment provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material. In addition to the technical solutions of the above embodiments, it also has the following technical features. The striking component 6 includes: A bracket 60 is mounted on the clamping jaw 50; The striking head 61 is slidably mounted on the bracket 60, and one end of the striking head extends out of the bracket 60 to strike the side of the cold pressing mold 3; The first spring 62 is installed in the bracket 60 and is used to push the knocking head 61 to knock the side of the cold pressing mold 3; The electromagnet 63 is installed in the bracket 60 and is used to attract the striking head 61 to compress the first spring 62 when powered on; An electric control unit 64 is installed in the bracket 60 and is used to turn on and off the electromagnet 63; The second driving member 65 is mounted on the clamping jaw 50 and is used to drive the electric control unit 64 to sequentially turn on and off the electromagnet 63; The striking head 61 may be made of a material that can be adsorbed by the electromagnet 63 , such as iron, or an iron rod / iron block may be installed on a side of the striking head 61 close to the electromagnet 63 .

[0029] It can be seen from the present embodiment that the electromagnet 63 is used to adsorb the striking head 61, and after power is cut off, the surface of the cold pressing mold 3 is struck under the action of the first spring 62, thereby vibrating the cold pressing mold 3. At the same time, the electromagnet 63 is powered on and off by the electrical control unit 64, so that regular striking can be achieved, thereby ensuring the vibration effect, improving the mixing effect between the alloy powder and the steel wool, maintaining product quality, and improving the accuracy of the test data.

[0030] Embodiment 5: This embodiment provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material. In addition to the technical solutions of the above embodiments, it also has the following technical features. The electric control unit 64 includes: The fixed electrical contact 640 is mounted on the bracket 60 and includes a first electrical contact and a second electrical contact that are arranged correspondingly, and an electrical gap 641 is formed between the first electrical contact and the second electrical contact; The disc 642 is mounted at the output end of the second driving member 65 and is provided with a movable electrical contact 643 which can rotate with the disc 642 and be embedded in the electrical gap 641 for connecting or disconnecting the first electrical contact and the second electrical contact; Wherein, the first electrical contact and the second electrical contact are electrically connected to two terminals on the electromagnet 63 respectively; At the same time, the second driving member 65 can adopt a rotating shaft connected to the bearing of the clamping jaw 50, and the disc 642 is installed at one end of the rotating shaft located on the side of the cold pressing mold 3, and a driven gear is installed at the other end of the rotating shaft. The second driving member 65 also includes a driving motor and a driving gear installed on the output shaft of the driving motor. The rotating shaft is driven to rotate through the engagement of the driving gear and the driven gear.

[0031] It can be seen from the present embodiment that by adopting the setting of a fixed electrical contact 640 with an electrical gap 641, and arranging a movable electrical contact 643 on a rotating disk 642 that can conduct the two fixed electrical contacts 640, regular knocking can be achieved through the rotation of the motor, and the knocking frequency can be changed by controlling the rotation speed of the motor, thereby improving the convenience of control.

[0032] Embodiment 6: This embodiment provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, which, in addition to the technical solutions of the above embodiments, also has the following technical features: The movable electrical contact 643 includes a conductive contact and a non-conductive contact, and is provided in plurality and is arranged on the disk 642 at equal intervals around the circumference; There are multiple knocking assemblies 6, which are arranged around the cold pressing mold 3, and a neutral point 644 is formed between two adjacent fixed electrical contacts 640, so that when the non-conductive contacts correspond to them, all the electromagnets 63 are energized; The non-conductive electrical contacts may be made of materials such as plastic, so as to achieve the inability to conduct fixed electrical contacts 640; Meanwhile, the knocking assembly 6 and the fixed electric contact 640 can be 5 and arranged on the clamping jaw 50 on one side, and the axis angle between two adjacent knocking assemblies 6 is 30°, and the number of the movable electric contacts 643 is 24 and arranged on the disk 642 at equal intervals on the circumference, and the number of the conductive electric contacts is 22 and the number of the non-conductive electric contacts is 2. Specifically, the two non-conductive electric contacts are symmetrically arranged relative to the axis of the disk 642; The included angle between the center line of the neutral point 644 and the axis of the striking component 6 is 15°, that is, the neutral point 644 and the striking component 6 are arranged at equal intervals around the circumference.

[0033] It can be seen from this embodiment that by providing a plurality of knocking components 6 and surrounding the cold pressing mold 3, the multi-directionality of the knocking can be improved to ensure the mixing effect of the alloy powder and the steel wool; And the movable electrical contact 643 is set to be a conductive electrical contact and a non-conductive electrical contact, and an idle point 644 is formed between two adjacent fixed electrical contacts 640. When the non-conductive contact corresponds to it, all the electromagnets 63 are energized, that is, all the electromagnets 63 do not knock on the cold pressing mold 3, so as to ensure that the knocking vibration is weakened before knocking. The idle point is set to facilitate the mixing of the alloy powder and the steel wool by vibration, and at the same time ensure that the driving motor does not need to be started and stopped frequently. It only needs to control the rotation speed of the disc 642 to achieve the multi-directional knocking on the surface of the cold pressing mold 3 in sequence, and there is an idle period after each knocking, which is convenient for the vibration to mix the alloy powder and the steel wool. After a round of knocking, there is a long idle period, which is convenient for waiting for the vibration to stop. In this way, by controlling multiple rounds of repeated knocking, the mixing effect of the alloy powder and the steel wool is effectively guaranteed, and the product quality is guaranteed.

[0034] Embodiment 7: This embodiment provides a device for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material. In addition to the technical solutions of the above embodiments, it also has the following technical features, including: The limiting protrusion 10 is installed on the side wall of the bottom template 2 located at the cold pressing mold 3, and the bottom template 2 is provided with a mounting groove 11 for embedded installation of the limiting protrusion 10; The second spring 12 is arranged in the installation groove 11, and the two ends thereof are respectively in contact with the inner wall of the installation groove 11 and the limiting protrusion 10; The top block 13 is mounted on the bottom wall of the bottom mold plate 2 located on the cold pressing mold 3; The third spring 14 is arranged in the bottom template 2, and the two ends thereof are respectively in contact with the bottom template 2 and the top block 13; The limiting protrusion 10 is located at an angle at one end of the cold pressing mold 3 entering the bottom mold plate 2 .

[0035] It can be seen from the present embodiment that, through the setting of the limiting protrusion 10 and under the action of the second spring 12, it can be effectively ensured that when the cold pressing mold 3 is put back on the bottom template 2 after being knocked, the coaxiality between the cold pressing mold 3 and the core 9 can be ensured, and it is ensured that after the subsequent core 9 is pressed down, it can enter the cold pressing mold 3 for pressing and molding, and the setting of the top block 13 and the third spring 14 makes the cold pressing mold 3 always protrude from the surface of the bottom template 2, thereby facilitating the clamping of the cold pressing mold 3 by the clamping jaws 50, thereby improving convenience; At the same time, after the subsequent upper mold 8 is pressed down, the cold pressing mold 3 can be pushed into the bottom mold plate 2, and after the pressing and forming, it is convenient to push up the cold pressing mold 3, so as to facilitate the blanking of the cold pressing mold 3; The limiting protrusion 10 is located at an angle at one end where the cold pressing mold 3 enters the bottom mold plate 2 , which can facilitate the cold pressing mold 3 to enter the installation groove 11 and further push the limiting protrusion 10 into the installation groove 11 .

[0036] The embodiments of the present application are described above in conjunction with the accompanying drawings. In the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material, characterized in that: The following steps are involved: S1: Steel wool with a diameter of 30 μm is evenly placed in a cylindrical cold pressing mold with a diameter of 40 mm; S2: filling the alloy powder mechanically doped with hydroxyapatite powder around the steel wool; S3: The cold pressing mold is vibrated at high frequency for 10 minutes so that the alloy powder fully fills the cold pressing mold and the height of the upper layer of powder is flush with the steel wool; S4: pressing and molding in a cold pressing mold at a pressure of 5-50 MPa and maintaining the pressure for 5-20 minutes to obtain a green body; S5: placing the green body in S4 in a muffle furnace heated to 250-350° C. and sintering for 0.5-2 hours to obtain a powder metallurgy part; S6: The powder metallurgy part in S5 is placed in a muffle furnace heated to 250-380°C for 0.5-1 hour, and then quickly placed in an extrusion barrel with an extrusion ratio of 16:1, and hot extruded at a speed of 30 mm / s using a twin-shaft extruder to obtain a round rod with a diameter of 10 mm; S7: Use wire cutting to symmetrically cut the round rod in S6 into square rods with a thickness of 4-6 mm and a length of 100 mm, and then put them into a muffle furnace heated to 200-350°C and preheat for 0.5-2 hours; S8: hot rolling the square bar to a hot rolled plate with a total reduction of 50-95% by 2-10% reduction per pass, and preheating in a muffle furnace for 5 minutes between each pass; S9: After air cooling to room temperature, obtain a hot-rolled plate sample or a hot-rolled foil sample.

2. The method for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 1, characterized in that: The particle size of the mechanically doped hydroxyapatite powder in the alloy powder in S2 is 0.05~2μm, and the mass ratio is 0.5~15%.

3. The method for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 1, characterized in that: The alloy powder in S2 is atomized Zn-xCu (x=0.2~10wt.%) alloy powder, and the particle size is 30~1000 mesh.

4. The method for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 1, characterized in that: In S2, the mass ratio of steel wool to Zn-xCu alloy powder is 1:2~30.

5. A device used in the method for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to any one of claims 1 to 4, characterized in that: include: A base (1) is installed with a bottom template (2), a cold pressing mold (3) is installed on the bottom template (2), and the cold pressing mold (3) is provided with a cavity (4); A vibration mechanism is mounted on the base (1) and is located on the side of the bottom mold plate (2), and comprises a lifting component (5) for lifting the cold pressing mold (3) and a knocking component (6) for vibrating the cold pressing mold (3); The upper mold plate (7) is installed in a lifting manner above the bottom mold plate (2) and is provided with an upper mold (8) corresponding to the cold pressing mold (3), and a core (9) adapted to the mold cavity (4) is installed on the upper mold (8).

6. The device for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 5, characterized in that: The lifting assembly (5) comprises: A clamping jaw (50) is slidably connected to the base (1) and is used to clamp the cold pressing mold (3); A first driving member (51) is mounted on the base (1) and is used to drive the first driving jaw (50) to slide on the base (1); The lifting member (52) is mounted on an end of the clamping jaw (50) away from the cold pressing die (3) and is used to drive the clamping jaw (50) to lift.

7. The device for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 6, characterized in that: The striking component (6) comprises: A bracket (60) mounted on the clamping jaw (50); A striking head (61) is slidably mounted on the bracket (60), and one end of the striking head extends out of the bracket (60) to strike the side of the cold pressing mold (3); A first spring (62) is installed in the bracket (60) and is used to push the striking head (61) to strike the side of the cold pressing mold (3); An electromagnet (63) is installed in the bracket (60) and is used to absorb the striking head (61) to compress the first spring (62) when power is supplied; An electric control unit (64) is installed in the bracket (60) and is used to turn the electromagnet (63) on and off; The second driving member (65) is mounted on the clamping jaw (50) and is used to drive the electric control unit (64) to sequentially switch the electromagnet (63) on and off.

8. The device for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 7, characterized in that: The electric control unit (64) comprises: A fixed electrical contact (640) is mounted on the bracket (60) and comprises a first electrical contact and a second electrical contact which are arranged correspondingly, and an electrical gap (641) is formed between the first electrical contact and the second electrical contact; A disc (642) is mounted on the output end of the second driving member (65) and is provided with a movable electrical contact (643) capable of rotating with the disc (642) and being embedded in the electrical gap (641) for connecting or disconnecting the first electrical contact and the second electrical contact; The first electrical contact and the second electrical contact are respectively electrically connected to two connection terminals on the electromagnet (63).

9. The device for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 8, characterized in that: The movable electrical contacts (643) include conductive contacts and non-conductive contacts, and are provided in plurality and are arranged on the disk (642) at equal intervals around the circumference; There are a plurality of striking assemblies (6) disposed around the cold pressing die (3), and a neutral point (644) is formed between two adjacent fixed electrical contacts (640) so that when a non-conductive contact corresponds to the neutral point, all the electromagnets (63) are energized.

10. The device for preparing the hydroxyapatite-doped zinc-copper powder metallurgy degradable bone implant material according to claim 6, characterized in that: Also includes: The limiting protrusion (10) is mounted on the side wall of the bottom template (2) located on the cold pressing mold (3), and the bottom template (2) is provided with a mounting groove (11) for embedded installation of the limiting protrusion (10); A second spring (12) is disposed in the mounting groove (11), and two ends thereof are respectively in contact with the inner wall of the mounting groove (11) and the limiting protrusion (10); A top block (13) is mounted on the bottom wall of the bottom mold (2) and the cold pressing mold (3); The third spring (14) is arranged in the bottom template (2), and two ends thereof are respectively in contact with the bottom template (2) and the top block (13).

Citation Information

Patent Citations

  • Degradable nano-hydroxyapatite magnesium-based composite material and preparation method thereof

    CN112717198A

  • Stainless steel seamless steel pipe bending device

    CN116159900A

  • Preparation method of steel wool toughened zinc-based powder metallurgy degradable biomedical material with large-area galvanic corrosion structure

    CN118416294A

  • Metal powder pressurizing machine

    CN218744846U

  • A punching device for bolt production

    CN221018300U